Cholesterol accumulation, lipid droplet formation, and steroid production in Leydig cells: Role of translocator protein (18‐kDa). (9th December 2019) - Chung, Jin‐Yong; Chen, Haolin; Papadopoulos, Vassilios; Zirkin, Barry
Abstract: Background: Cholesterol import into the mitochondria of steroid‐producing cells is the rate‐determining step in steroidogenesis. Numerous studies have provided evidence that the cholesterol‐binding translocator protein (18 kDa TSPO) plays an important role in cholesterol translocation into mitochondria and that it also might act on cholesterol homeostasis. Several TSPO‐specific ligands have been shown to increase steroid production in vitro and in vivo. Objectives: The present study assessed the effects of the TSPO drug ligand FGIN‐1‐27 on cholesterol accumulation and lipid droplet formation in relationship to steroid formation. Materials and Methods: Using MA‐10 and primary Leydig cells, immunocytochemical and molecular methods were used to examine cholesterol accumulation, the formation of lipid droplets, and steroid formation in response to LH and FGIN‐1‐27. Additionally, we determined the effects of Tspo knockout by CRISPR/Cas9, and of siRNA knockdowns of Tspo and Plin2 (Perilipin 2; also known as adipose differentiation‐related protein, ADFP) on LH‐ and FGIN‐1‐27‐induced steroidogenesis. Results: In response to LH and FGIN‐1‐27, cultured MA‐10 cells and primary Leydig cells increased steroid formation, cholesterol accumulation, and lipid droplet formation. Cholesterol accumulation in the lipid droplets also was increased in Tspo knockout cells. Knockout of Tspo or its knockdown in MA‐10 cells resulted in reduced progesterone formation in response to both LH and FGIN‐1‐27, as did knockdown of Plin2 . Steroid production also was inhibited by the cholesteryl ester hydrolase inhibitor diethylumbelliferyl phosphate. Discussion and Conclusion: These results support the conclusion that FGIN‐1‐27 stimulates steroid formation by increasing TSPO‐mediated cholesterol translocation into the inner mitochondria for steroidogenesis, as well as into the cytosol for lipid droplet formation. FGIN‐1‐27 also increased steroid formation at least in part by inducing the conversion of cholesteryl ester located in lipid droplets to cholesterol, thus making available more substrate for steroid formation.